Validación de una escala para medir las Motivaciones para estudiar Medicina (MEM-12) en estudiantes Latinoamericanos - Mayta-Tristán, P. (2015)
Background: One’s motivations to study medicine as a career might play an important role in the performance of the future professional. Objective: To validate a motivation for choosing medicine scale in Latin American medical students. Methods: We carried out a cross-sectional multi-centered study including a sample of medical students from eight Spanish-speaking countries. Using a previously adapted Spanish scale and previous qualitative research, an initial 24- ítem Likert-like scale was generated, and subjects’ comprehension of this scale was tested in a pilot study. We calculated item-test correlation. Exploratory factor analysis (EFA) using principal component analysis with oblimin rotation and Kaiser Normalization was performed. Statistical determination of the number of factors was based on the Kaiser criterion, the Cattell scree plot and an explained variance of 5%. Assignment of items was based on weak loadings greater than 0.35. Internal consistency was measured using Cronbach’s alpha (α). Results: 435 subjects were suitable for analysis; 55% were male subjects and the mean age was 21.7±2.7 years. Two items were excluded due to a low itemtest correlation. EFA initially showed five factors; however, three of them did not have adequate internal consistency and their exclusion did not affect the global internal consistency of the questionnaire. Finally, two six-item factors were included; i) social/altruistic (α=0.80) and ii) economic/prestige (α=0.71), revealed which together explained 45.5% of the variance and revealed an adequate global internal consistency (α=0.74). Conclusions: The generated scale is valid and reliable, and comprises two factors representing social and economic motivations. We recommend its use in assessing motivations regarding the choice of a medical career in Latin America.